2006
DOI: 10.1074/jbc.m507367200
|View full text |Cite
|
Sign up to set email alerts
|

Selective Role of Intracellular Chloride in the Regulation of the Intrinsic but Not Extrinsic Pathway of Apoptosis in Jurkat T-cells

Abstract: Apoptosis is a genetic program for the removal of unwanted cells from an organism, which is distinct from necrosis by its characteristic volume loss or apoptotic volume decrease. This cell shrinkage is the result of ion redistribution that is crucial for both the activation and execution of apoptosis. Here we report that UV-C but not Fas ligand treatment results in a significant decrease in intracellular chloride that can be abolished by modulation of chloride flux using either the chloride channel inhibitor S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 46 publications
(65 reference statements)
5
48
0
Order By: Relevance
“…(16). It is noted that inhibition of Cl Ϫ loss not only limits cell shrinkage but also prevents DNA degradation in human Jurkat cells following intrinsic activation of the apoptotic process (14). Inhibition of K ϩ loss will likewise limit the initial cell shrinkage but presumably also restrict decay of the membrane potential, which would normally favor Ca 2ϩ influx and activation of apoptotic enzymes (32,35,67).…”
Section: Resultsmentioning
confidence: 99%
“…(16). It is noted that inhibition of Cl Ϫ loss not only limits cell shrinkage but also prevents DNA degradation in human Jurkat cells following intrinsic activation of the apoptotic process (14). Inhibition of K ϩ loss will likewise limit the initial cell shrinkage but presumably also restrict decay of the membrane potential, which would normally favor Ca 2ϩ influx and activation of apoptotic enzymes (32,35,67).…”
Section: Resultsmentioning
confidence: 99%
“…FasL induces the activation of ORCC; however, net Cl Ϫ depletion does not occur during FasL-induced apoptosis, and thus, changes in intracellular Cl Ϫ distribution do not participate in the progression of cell death (62). We focused then on the role of K ϩ depletion in apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanism by which the reduction in GSH i modulates the activation of the execution phase of apoptosis is still imprecise. A necessary role of K ϩ loss for the activation of execution caspases and apoptosome formation has also been demonstrated (5,60,61), whereas Cl Ϫ loss does not seem to play an important role in this phenomenon (62). Thus, we analyzed if the modulation of the execution phase of apoptosis by GSH transport was linked to the regulation of K ϩ loss.…”
Section: Gsh Regulates the Execution Phase Of Apoptosis By The Modulamentioning
confidence: 91%
“…Interestingly, it has also been proposed that Cl -channels may play a dual role depending on the specific type of cell death, such that Cl -channels have a protective effect if activated during necrosis, while having a cell-killing effect if activated during apoptosis [114]. Recently, Heimlich and Cidlowski [115] showed that the Cl -channel blocker SITS or medium with reduced chloride concentration diminished UV-C induced apoptosis in Jurkat T-cells, but was ineffective in preventing apoptosis induced through the death receptor pathway.…”
Section: Chloride As a Counter-ionmentioning
confidence: 99%